Collaborative Governance dalam Mewujudkan Kota Layak Anak di Kota Palu - Nawawi, Moh.; Rusdin, Rusmawaty Bte (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2025)
Child abuse cases are often a problem that always occurs from year to year, children are often the object of violence ranging from physical to psychological violence.  In an effort to protect children, the Indonesian government has issued a Child Friendly City policy. Palu City has implemented a child-friendly city policy and has pursued various programmes that support the fulfilment of children's rights. Collaborative governance in realising a child-friendly city in Palu City is the subject of this research. This research hypothesis is based on Ratner's Collaborative Governance theory (2012) which includes the following indicators: 1) Identifying opportunities and challenges, 2) Discussing ways to influence others, and 3) Working together. Descriptive qualitative research including observation, interviews, and documentation was the methodology used. The research findings show that by involving children and other members of the KLA Task Force, Collaborative Governance has succeeded in making Palu City a child-friendly city. In order to build a child-friendly environment supported by all components involved, the government has also made a number of initiatives. The following factors hinder collaborative efforts to create a child-friendly city in Palu City: the lack of public awareness of child-friendly city programmes or policies is another obstacle that needs to be addressed immediately; and the turnover of actors causes progress or synergy to become stagnant, thus requiring repeated strengthening in order to form better synergies.